Pengaruh Motivasi Dan Religiusitas Terhadap Kinerja Karyawan Pada Unit Usaha Syariah Bank 9 Jambi Kota Jambi - Fadhlidzil Ikram; Lucky Enggrani Fitri; Ary Dean Amri (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the impact of motivation and religiosity on employee performance at the Unit Usaha Syariah Bank 9 Jambi. This research employs a quantitative approach with a survey method. Data was collected using a questionnaire distributed to 34 employees of the bank, measured using a Likert scale. The data analysis technique used is multiple linear regression. The results show that motivation has a significant positive effect on employee performance, with a regression coefficient of 0.364 and a significance level of 0.000. Similarly, religiosity has a significant positive effect on employee performance, with a regression coefficient of 0.481 and a significance level of 0.002. Simultaneously, both motivation and religiosity have a significant effect on employee performance, with an F-value of 18.431 (p < 0.05). These findings suggest that both motivation and religiosity play a crucial role in enhancing employee performance in the Islamic banking sector. It is recommended that Unit Usaha Syariah Bank 9 Jambi continue to consider motivation and religiosity in its managerial policies to improve employee performance. This research also opens opportunities for future studies to examine other factors influencing employee performance.